Factors Impacting the Sustainability of Supply Chain in Industry 5.0: An Exploratory Qualitative Study in Morocco - Molk Oukili Garti; Jabir Arif; Fouad Jawab; Youness Frichi; Fatima Zahra Benbrahim (Logistics)
Background: The objective of this qualitative research was to explore the impact of certain predefined factors on the sustainability of supply chains in Industry 5.0. The sustainability of supply chains was assessed by considering six factors from the existing literature: circular logistics, Industry 5.0 technologies, intellectual level and learning, logistics innovation, sustainable supply chain practices, and the managerial strategy of the company. Methods: Semi-structured interviews were conducted based on an interview guide with 14 participants who serve as managers and executives in supply chain management in Morocco. The interviews were transcribed, followed by lexical and thematic analysis using QSR NVivo 15 software. Results: The results showed that all the factors studied play a major role in achieving sustainable supply chain management. The testimonies of all participants highlighted the crucial role that Industry 5.0 technologies play in achieving the sustainability of supply chains, while combining them with the other factors studied. Consequently, these results made it possible to validate and confirm the six factors previously identified from the existing literature, while retaining them for potential future quantitative studies. Conclusions: To meet the dimensions of sustainability, it is recommended to focus on the most impactful factors in maintaining a sustainable supply chain and on all the possible interactions between these factors. Indeed, this study represents, on the one hand, an invitation for supply chain managers to pay greater attention to factors related to sustainability, and on the other hand, an initial pathway for future research that may subsequently highlight the interactions between factors leading to sustainability. This could help propose applicable models for supply chain managers, enabling them to adopt more effective strategies and identify the most feasible combinations of factors to achieve sustainable logistics.